Calculation of electron scattering from the ground state of ytterbium - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2011)
We report on the application of the convergent close-coupling method, in both relativistic and nonrelativistic formulations, to electron scattering from ytterbium. Angle-differential and integrated cross sections are presented for elastic scattering and excitation of the states (6s6p)3P0,1,2, (6s6p)1P1o, (6s7p)1P1o, and (6s5d)1D2e for a range of incident electron energies. We also present calculations of the total cross section, and angle-differential Stokes parameters for excitation of the (6s6p)3P1o state from the ground state. A comparison is made with the relativistic distorted-wave method and experiments.